2022
DOI: 10.1016/j.molp.2021.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Dual and opposing roles of EIN3 reveal a generation conflict during seed growth

Abstract: Seed size critically affects grain yield of crops and hence represents a key breeding target. The development of embryo-nourishing endosperm is a key driver of seed expansion. We here report unexpected dual roles of the transcription factor EIN3 in regulating seed size. These EIN3 functions have remained largely undiscovered because they oppose each other. Capitalizing on the analysis of multiple ethylene biosynthesis mutants, we demonstrate that EIN3 represses endosperm and seed development in a pathway regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
0
5
1
Order By: Relevance
“…ROS signaling is interconnected with the response to several phytohormones, especially the gaseous hormone ethylene. Production of ethylene and the activation of ethylene responses have been reported to belong in vegetative development as the first events following the accumulation of ROS 40,41 In Arabidopsis , it has been previously shown that ethylene signaling 17,18,42 , bot not necessarily the hormone itself 18 , is required for the degeneration of the persistent synergid cell and the establishment of a pollen tube block. To dissect the contributions of ethylene and ethylene signaling to synergid cell death, we therefore first investigated the dynamic expression changes of genes related to ethylene biosynthesis and signaling.…”
Section: Resultsmentioning
confidence: 99%
“…ROS signaling is interconnected with the response to several phytohormones, especially the gaseous hormone ethylene. Production of ethylene and the activation of ethylene responses have been reported to belong in vegetative development as the first events following the accumulation of ROS 40,41 In Arabidopsis , it has been previously shown that ethylene signaling 17,18,42 , bot not necessarily the hormone itself 18 , is required for the degeneration of the persistent synergid cell and the establishment of a pollen tube block. To dissect the contributions of ethylene and ethylene signaling to synergid cell death, we therefore first investigated the dynamic expression changes of genes related to ethylene biosynthesis and signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ROS content also did not differ between the wild type and the oseil1 mutant under the NH 4 + treatment (Figure ). In a recent study, dual and opposing roles of AtEIN3 revealed a 'generation conflict' during seed growth in Arabidopsis , and AtEIN3 was shown to possess both ethylene‐dependent and ‐independent regulatory functions in seed growth (Heydlauff et al, 2021). The present and previous studies suggest that the functional complexity of the EIN3 gene product and the products of its homologous genes varies with developmental stage and among species.…”
Section: Discussionmentioning
confidence: 99%
“…Polytubey block is completed by the degeneration of the persistent synergid triggered by double fertilization. The degeneration processes include a cell-fusion between the persistent synergid and endosperm (Maruyama et al, 2015) and degeneration of the persistent synergid nucleus, which is mediated by the EIN3 and EIL1 transcription factors (Völz et al, 2013; Li et al, 2022; Heydlauff et al, 2022) and FIS-class polycomb repressive complex (Maruyama et al, 2013; Maruyama et al, 2015). Compared to these late degeneration processes, the disappearance of actin cables may be an earlier and fertilization-independent alteration that temporarily inactivates persistent synergid functions (Figure 8F, 8I, 8J–K).…”
Section: Discussionmentioning
confidence: 99%